Rasch-Built Measure of Pleasant Touch through Active Fingertip Exploration - Klöcker, Anne; Penta, Massimo; Arnould, Carlyne; Thonnard, Jean-Louis (Frontiers in Neurorobotics, 2012)
BACKGROUND: Growing evidence exists that the somatic sensation has a modality for pleasant touch. OBJECTIVE: Investigate pleasant touch at fingertip level (i.e. glabrous skin site) through the elaboration of a linear unidimensional scale locating (i) various materials according to their pleasantness level they elicit through active fingertip explorations and (ii) subjects according to their pleasantness leniency levels. SUBJECTS: 198 healthy subjects without any neurological disease participated in this study. METHODS: Blindfolded subjects actively explored 48 materials with their index fingertip and reported, for each material, their perceived pleasantness of touch on a 4-level scale. The subjects’ fingertip moisture levels were measured before the experimental session. The data has been analysed by using the Rasch model. RESULTS: An unidimensional linear scale has been elaborated. This scale locates 37 materials according to the pleasantness of touch they elicit through active touch explorations. Furthermore, the pleasantness level of 21 materials was differently perceived depending on the subjects’ fingertip moisture levels. Each of these 21 materials defines a low- and a high- moisture item. CONCLUSION: A Pleasant Touch Scale has been elaborated. The investigations indicate that the fingertip moisture level appears to be a major factor of the (un)pleasant feeling during active explorations.